PHARMACOGNOSTIC STUDIES AND DEVELOPMENT OF QUALITY CONTROL PARAMETERS FOR LEAVES OF ALBIZIA CHEVALIERI HARMS (FABACEAE) - Imam, K. I.; Ahmed, A.; Ilyas, N.; Nuhu, A. (FUDMA Journal of Sciences, 2023)
Albizza chevalieri harms is a tree or shrub of 5 - 12 m tall and distributed in the dry savannah from Senegal, Niger and Nigeria. In traditional medicine, the leaf is used in treatment of purgative, dysentery, diarrhoea, taeniasis and also remedy for coughs. The present study was carried out to determine some important pharmacognostic parameters of A. chevalieri leaf which will assist in standardization for quality, purity and sample identification. Pharmacognostic standardization of the leaf was assessed based on the macromorphological, micromorphological, chemomicroscopic and some physicochemical parameters. The leaf is greenish in colour and microscopy features showed epidermis to be hypostomatic with numerous paracytic type of stomata, and lignified hair trichomes, prismatic and acicular crystals of calcium oxalates, vascular bundles, fibres, and the epidermal cells of wavy or irregular in shape on both surface with straight anticlinal walls. Study of transverse section of the leaf revealed its dorsiventral nature. Chemomicroscopy showed the presence of tannins, starch, cuns and cellulose. Quantitative leaf constants revealed the stomatal number (22.33), stomatal index (21.54), palisade ratio (17.25), vein islets number (5.00) and veinlet termination number (6.65). Physicochemical parameters such as moisture content/loss on drying (9.11), total ash content (6.65), water soluble ash content (1.75), acid insoluble ash content (1.5) and ethanol had high extractive value of (21.00) compared to water which had extractive value of (15.62). The pharmacognostic parameters observed in this study will be of help in correct identification and quality control of A. chevalieri.